2011
DOI: 10.21608/jfds.2011.81949
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF FERMENTATION OF FABA BEAN (Vicia faba) ON ITS NUTRITIVE AND SENSORY PROPERTIES

Abstract: Evaluation the effect of using different microbial strains in the fermentation of Faba Bean on its nutritive value and consumer acceptance was performed. Fermentation of processed Faba Bean (autoclaved and non autoclaved) with lactobacillus acidophilus (LAB), Bacillus Subtilis (B.subtilis) and Saccharomyces cerevisiea (Yeast) were performed for 44 hrs after which analysis of chemical composition and anti-nutritional factors were performed to estimate the major differences before and after fermentation process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…In this work, body protein retention was 7% higher in young rats fed fermented faba bean–dairy gels containing whey proteins than in fermented faba bean gels made without whey proteins [120]. Furthermore, we observed higher whole-body protein retention in young rats fed the dairy gels enriched with 50% faba bean proteins than the retention observed by El-Moghazy et al [121] in rats fed fermented faba bean proteins alone. Further research is needed to test the ability of this faba bean–dairy mixed gel to stimulate postprandial muscle protein synthesis and thereby support muscle mass in older subjects.…”
Section: Main Strategies To Improve the Anabolic Properties Of Plasupporting
confidence: 53%
“…In this work, body protein retention was 7% higher in young rats fed fermented faba bean–dairy gels containing whey proteins than in fermented faba bean gels made without whey proteins [120]. Furthermore, we observed higher whole-body protein retention in young rats fed the dairy gels enriched with 50% faba bean proteins than the retention observed by El-Moghazy et al [121] in rats fed fermented faba bean proteins alone. Further research is needed to test the ability of this faba bean–dairy mixed gel to stimulate postprandial muscle protein synthesis and thereby support muscle mass in older subjects.…”
Section: Main Strategies To Improve the Anabolic Properties Of Plasupporting
confidence: 53%
“…The improvement effect of FFB on growth performance of broilers may be attributed to the lowering of ANFs in legumes after fermentation and increasing nutrient absorption and utilization (49). Similar studies have shown that microbial fermentation is an efficient process to eliminate ANFs and tannins in legume feed, thereby enhancing the nutritional quality and improving the performance of broilers (50). With fermentation, fava bean oligosaccharides and NSPs become more available for cecal microbes that facilitate their digestion (51).…”
Section: Figure 3 |mentioning
confidence: 94%